2016
DOI: 10.7763/ijssh.2016.v6.701
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Job Stress and Front-liners’ Job Performance in a Shared Service Center in Malaysia

Abstract: Abstract-The purpose of this study is to examine the relationship between job stress and job performance of front-liners in a shared service center, Malaysia. The conceptual framework of this study is based on the model of Job Stress (role ambiguity, role conflict, inadequate resources, and workload) and the concept of job performance. A total of 113 front-liners from various departments in a shared service center were selected as respondents through convenience sampling technique. Findings indicated that job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…Studies showed that it is a significant determinant of employee productivity and performance. [24][25][26] It is a major problem for such employees that fail to balance the competing demands of work and family. It significantly influenced the productivity of employees without spouses and young employees that WFH.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that it is a significant determinant of employee productivity and performance. [24][25][26] It is a major problem for such employees that fail to balance the competing demands of work and family. It significantly influenced the productivity of employees without spouses and young employees that WFH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is the psychological and physical state that results when the resources of the individual are not sufficient to cope with the demands and pressures of work situations or family affairs or both. Studies showed that it is a significant determinant of employee productivity and performance 24–26 . It is a major problem for such employees that fail to balance the competing demands of work and family.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an example of this, it has been determined that front-line staff otherwise known as the front of the house staff have one of the top ten most stressed induced jobs in the US, which in turn might be brought home by the employee in a spillover effect. This may cause burnout (Syazreena Azmi, Shahid & Alwi, 2016).…”
Section: Job Characteristics and Their Effect On Employee Burnoutmentioning
confidence: 99%
“…Beban kerja dapat didefinisikan sebagai keengganan untuk datang bekerja dan perasaan tekanan konstan (yaitu tidak ada upaya yang cukup) disertai dengan gejala stres fisiologis, psikologis, dan perilaku umum (Syazreena Azmi, Asiah Md. Shahid, & Alwi, 2016). Beban kerja yang berlebihan merupakan sumber stres di tempat kerja dan kelelahan emosional (Karatepe, 2013).…”
Section: Gambar 3 Garis Kontinum Variabel Karakteristik Individuunclassified